Kropp, blick och plats – konstruktioner av dans- och vokalundervisning - Borgström Källén, Carina Lena Marie; Sandström, Birgitta (Educare, 2019)
By focusing on dance and on the voice as a music instrument, and applying a gender perspective, this article problematizes constructions of dance and music education – arenas where girls and women are in the majority. The result is based on the meta-analysis of a common issue found in four qualitative studies, three conducted at the aesthetic programs at upper-secondary schools in Sweden and one conducted in higher music education. The studies were produced through participatory observation, video-documented teaching situations, discussions with teachers about critical incidents, focus group discussions and group interviews. The meta-analysis shows that dance and vocal studies’ have similar subject constructions based on the traditions and conventions of the performing arts. Furthermore, the result points to the need to highlight how the body, the gaze, and the place are constructed in teaching and learning to clarify what norms and values ​surround the subjects. The article contributes to the discussion of how quality is understood in dance and music education and increases the knowledge of widening participation in these subjects.